SYSTEMATIC LITERATURE REVIEW : KEBERAGAMAN CARA BERPIKIR SISWA DALAM PEMECAHAN MASALAH MATEMATIS DITINJAU DARI SELF-EFFICACY - Shelly Morin; Tatang Herman (IKIP Siliwangi, 2022)
This research is motivated by the fact that each student's different way of thinking in dealing with problems will produce different solutions. This different way of thinking is influenced by the schemata of knowledge that are formed in each other's minds. so that diversity can describe the way students think in the learning process, especially in solving problem solving problems. In this case, self-efficacy acts as an affective aspect that affects how students think, motivate themselves, and build confidence in students in the learning process. Therefore, this study aims to conduct a literature review related to the diversity of students' ways of thinking in solving mathematical problems in terms of self-efficacy. The research method chosen in this research is a systematic literature study. Data collection was obtained from the Google Schoolar database using the Publish or Perish application. The results of this study can contribute to further research for researchers who compile research on this issue.